2017
DOI: 10.1021/acs.orglett.7b00691
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Oxo-Tethered Ruthenium Complex Catalyzed Asymmetric Transfer Hydrogenation of Aryl N-Heteroaryl Ketones

Abstract: A facile asymmetric transfer hydrogenation of ortho-substituted aryl N-heteroaryl ketones and non-ortho-substituted N-oxide of aryl N-heteroaryl ketones using a readily available oxo-tethered ruthenium complex as a catalyst and sodium formate as a hydrogen source in an aqueous solution has been discovered. A variety of chiral aryl N-heteroaryl methanols were obtained with up to 99.9% ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Most of the reported works use nitrogen atmosphere, temperature of 82 °C, and catalyst load between 0.1 to 1 mol % [29,38,39]. A recent work employed temperatures of 40 and 50 °C, a catalyst load of 5%, and reaction time between 24 to 30 h [40]. These results indicate that the conditions carried out here are very mild, because we do not use inert atmosphere, the temperature is lower, the reaction time is acceptable, the catalyst load is similar, and the in situ conditions were completely done in the NMR equipment, approaching a combined methodology between rapid injection and static tube.…”
Section: Catalytic Studies By Nmrmentioning
confidence: 99%
“…Most of the reported works use nitrogen atmosphere, temperature of 82 °C, and catalyst load between 0.1 to 1 mol % [29,38,39]. A recent work employed temperatures of 40 and 50 °C, a catalyst load of 5%, and reaction time between 24 to 30 h [40]. These results indicate that the conditions carried out here are very mild, because we do not use inert atmosphere, the temperature is lower, the reaction time is acceptable, the catalyst load is similar, and the in situ conditions were completely done in the NMR equipment, approaching a combined methodology between rapid injection and static tube.…”
Section: Catalytic Studies By Nmrmentioning
confidence: 99%
“…For example, chiral β‐hydroxysulfones were synthesized from readily available terminal alkynes and sodium sulfinates via oxysulfonylation and asymmetric transfer hydrogenation [10] . To continue our interest in asymmetric transfer hydrogenation of aryl N ‐heteroaryl ketones, [9a,b,h] we report a one‐pot asymmetric stepwise reductive amination of aryl N ‐heteroaryl ketones with benzyl amines without isolation of the unstable ketimines, using p ‐toluenesulfonic acid as a catalyst for the formation of imines, chiral iridium complex as a catalyst and a mixture of formic acid/triethylamine as a reductant for the tandem asymmetric transfer hydrogenation, affording chiral aryl N ‐heteroaryl methylamines in up to 99% ee (Scheme 1d).…”
Section: Introductionmentioning
confidence: 99%
“…Versatile ruthenium(II) 2-aminomethylpyridine (ampy) complexes have been reported by Baratta et al [44][45][46][47][48][49] and demonstrated very high catalytic activity in the TH and asymmetric TH (ATH) of ketones. Moreover, Noyori ruthenium(II) complexes, containing N-sulfonylated 1,2-diamines as chiral ligands, have been used as efficient catalysts for the ATH of ketones and imines [50][51][52][53][54][55]. Furthermore, transition-metal complexes bearing a ligand with NH functionality also exhibit high catalytic activity in transfer hydrogenation reactions [56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%